VOIP Model for ICT Rural Communities Telecentre in Sintok - Mohmad, Alateeby Saad (2012)
Transmission of Voice over Internet Protocol (VoIP) on packet switching networks is one of the rapidly emerging real-time applications. VoIP is a formation of audio and voice communication. It receive voice signal activities then encoded in digital form and divided into small parts of information as like voice data network packets. These data network packets are decoded and transmitted voice in signals then sender and receiver having a voice conversion. In a voice conversion, the clients send and receive packets in a bidirectional method. Each client work as a sender and as a receiver depends on the direction of traffic flow over network. The aim of this proposal is to propose a VOIP model for ICT rural community’s telecaster in Sintok.